Pembangunan Pertanian Berbasis Kecerdasan Masyarakat - Murasa Sarkaniputra (Universitas Islam Indonesia, 2004)
The goal and the orientation of long term Indonesian development are a just and prosperous society based on Pancasila. To reach this long run Indonesian development afore-mentioned can be conducted by several steps either that applied by old order, new order or that of reformation era. The vision of the development actually is nation and Character building. Contrary to the vision of Indonesian development that appear negative phenomena from the actors of Indonesian development above mentioned, for instance coalition, corruption and nepotism. To overcome the problems of Indonesian nation currently, this nation needs to develop community intelligence-based agricultural development.